A non-singular transformation optics invisibility cloak by combining with scattering cancellation. (31st January 2019) - Tay, C Y; Teniou, M; Roussel, H; Chen, Z N
Abstract: A mechanism-based method to suppress the transformation optics cloaking singularities is proposed. Using the invariance nature of the Maxwell's equations, instead of a point, a scattering cancellation cloaked circle is used as the virtual space for the transformation. The advantages of the proposed method includes non-singular constitutive parameters and significantly reduced variation range. Singularity removal is proved analytically while invisibility is demonstrated numerically using COMSOL Multiphysics.